Pengaruh Penerapan Gaya Mengajar Demonstrasi terhadap Kemampuan Gerak Dasar pada Tendangan Samping Pencak Silat Peserta Didik Kelas VIII SMP Negeri 1 Remboken - Christian Thesda Rembet; Pinangkaan Pinangkaan; Tony Pandaleke (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
This study aims to test the application of the demonstration teaching style to improve basic movement abilities in side kicks in pencak silat. The method used in this research is the experimental method. The samples used were 20 students in class VIII of SMP Negeri I Remboken for the 2024/2025 academic year, who were divided into two groups, namely the experimental group with a demonstration teaching style totaling 10 samples and the control group which did not receive treatment totaling 10 samples. The research was carried out for one month with a frequency of three times a week. The research design used was "Randomized control group pre-test and post-test design. The results of this study show that the average increase in basic movement abilities in side kicks in the pencak silat experimental group using a demonstration teaching style is better (¯x_1=3.2) than the average increase in basic movement abilities in side kicks in the pencak silat control group. did not receive treatment (¯x_2=0.5). The conclusion of this research is that there is an influence of applying a demonstration teaching style on improving basic movement abilities in side kicks in pencak silat in class VIII students at SMP Negeri I Remboken.